Kupffer Cells: Important Participant of Hepatic Alveolar Echinococcosis - Liu, Yumei; Tian, Fengming; Shan, Jiaoyu; Gao, Jian; Li, Bin; Lv, Jie; Zhou, Xuan; Cai, Xuanlin; Wen, Hao; Ma, Xiumin (Frontiers in Cellular and Infection Microbiology, 2020)
Aims: Kupffer cells (KCs) are the liver-resident macrophages and play a leading role in the regulation of liver homeostasis in physiological conditions and in pathology.The study aimed to investigate the anti-echinococcosis effect of KCs and the effects of hepatic stellate cells (HSCs) activation on the progression of liver fibrosis in hepatic alveolar echinococcosis (hepatic AE).Methods: Hematoxylin -eosin (H&E) and Masson staining were used to assess the pathological inflammatory changes and collagen deposition respectively.Immunohistochemistry and qRT-PCR were used to detect the number of aggregates of KCs, the expression of cytokines and activation of HSCs.In the close group, H&E staining showed that the normal lobular structure was destroyed, inflammatory infiltration around the lesion could be observed and Masson staining showed that blue collagen fibers were clearly deposited near the portal area. IHC showed that KCs surface markers CD68 and CD163, cytokine iNOS and Arg-1 were positively expressed in the vicinity of inflammatory lesions. qRT-PCR indicated that TNF-α, IL-10 and TGF-β1 secreted by KCs were significantly higher than those in the distance group (P < 0.01). Interestingly, the expression levels of antiinflammatory cytokines were slightly higher than that of pro-inflammatory cytokines.Both IHC and qRT-PCR results showed that HSCs activation markers, the expression of α-SMA and Desmin was significantly increased.Our research indicates that KCs have immune-protective effect of antiechinococcosis and promote liver fiber repair, and suggest that they have potential therapeutic value for patients with hepatic AE.